Nanoscopy reveals integrin clustering reliant on kindlin-3 but not talin-1 - Yuanyuan Wu; Ziming Cao; Wei Liu; Jason G. Cahoon; Kepeng Wang; Penghua Wang; Liang Hu; Yunfeng Chen; Markus Moser; Anthony T. Vella; Klaus Ley; Lai Wen; et al. (Cell Communication and Signaling)
Summary 1. Kindlin-3 but not talin-1 contributes to integrin inside-out signaling induced β2 integrin clustering. 2. The Pleckstrin homology domain of kindlin-3 was critical for its mediated β2 integrin clustering.